IITA welcomes lead delegates from the World Bank - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In line with the World Bank’s commitment to fostering knowledge compacts and partnerships with scientific and innovative communities, IITA was pleased to welcome their efforts to explore avenues for scaling acquired knowledge to effectively reach farmers.